Impact of Bacillus subtilis QST713 mushroom grain spawn treatment on yield and green mould control - Potočnik, Ivana S; Todorović, Biljana; Rekanović, Emil; Luković, Jelena; Paunović, Dušanka; Milijašević-Marčić, Svetlana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2018)
A biofungicide based on Bacillus subtilis QST713 was tested for impact on yield and efficacy against a Trichoderma aggressivum f. europaeum T77 strain from Serbia by coating mushroom grain spawn and comparing the results with the chemical fungicide prochloraz manganese in a mushroom growing room. The tested B. subtilis QST713 strain did not inhibit mycelial growth of Agaricus bisporus in plots free of the pathogen, showing an impact on yield of 91.95%, which was not significantly different from an untreated control. As for the efficacy of the fungicides used against T. aggressivum f. europaeum T77, there were no significant differences between a prochloraz manganese casing treatment, and B. subtilis QST713 coating on mushroom grain spawn, as the efficacy was 70.37 and 53.09%, respectively. These results implied that the biofungicide based on B. subtilis could serve as a harmless alternative to synthetic fungicides in mushroom production, especially during serious compost green muold outbreaks caused by T. aggressivum. Furthermore, the biofungicide should be applied alone because an antagonistic reaction was detected between the fungicide prochloraz and B. subtilis QST713.
Keywords: Mushroom; Bacillus subtilis; Trichoderma; Fungicides